Formal research networking for results : an empirical study - Rakhmatullin, Ruslan (Trinity College (Dublin, Ireland). Trinity Business School, 2011)
The European Union (EU) is continuously increasing its support to a range of formal networking research (FNR) programmes of pre-competitive nature. This study brings together the fields of performance theory and research management with an aim to investigate the added-value created through researcher participation in such funded formal networking research projects. It builds a theoretical framework that reflects the objective of the proposed research which is to understand the nature of formal networking research funding scheme supported by the EU. This thesis selects COST (European Cooperation in Science and Technology) as an example of such a funding scheme. It explores the extent to which funding providers (progress assessing experts) expect specific FNR outputs to be achieved by FNR participants. It further examines the extent to which the specific research outputs are actually achieved by FNR participants and if their results correspond with expert expectations. Thirdly, this research suggests that participation in a FNR project assumes development or improvement of networking (collaborative) skills and improved researcher productivity. Data collection for this study included a number of methods from process observation and assessment to surveys. As this study primarily utilises a survey methodology, the empirical data is gathered in three cross-sectional surveys. This study further provides a comprehensive overview of the statistical test results conducted with the collected survey data. Next, this research explores the relationships between the different types of FNR productivity and other variables. Statistical analyses such as Principal Component Analysis technique and Multivariate Regression are conducted to investigate some of the relationships between these variables in depth. This study provides contributions of a methodological and theoretical nature. As researchers are still in the process of consolidating a general theory of collaboration, this study contributes to the body of knowledge by helping to further defragment pertinent studies.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin